From Data to Simulation: A dynamic shift fork analysis - Fahlgren, Elin; Åkesson, Edvin (My University, 2024)
In a truck’s AMT, gear shifting is performed by moving a sleeve with dog-clutch teeth, to change the load path through the transmission. A pneumatic cylinder pushes the system, which includes a rod, ring gear, and shift fork. Due to the fast transient dynamics, rapid shift and high dynamic loads of the system, an explicit dynamic FE model is used to simulate its behaviour. The aim is to build an FE model of the fork and validate it against empirical test data, as well as find the key parameters to describe the loads from a shift. Additionally, a regression was developed to predict the strain in the fork during tooth collisions. Boundary conditions, initial conditions, and forces included in the FE model were estimated from empirical data from 30 shifts. FEA was used to identify key parameters affecting the shift. The key parameters found were velocity and net force at impact. The finished model has a 20% average error for the first displacement peak, and a 32% average error for the second, compared to the empirical data. For the regression, the key parameters were the acceleration of the ring gear, the velocity of the rod, and the ring gear position at collision. The regression explains 55% of the strain variation. In conclusion, the project contains uncertainties due to the uniqueness of every shift. However, the FE results correspond well with the test data but future research into what damping should be used could enhance model accuracy.
Keywords: FEA; FEM; Explicit; ANSA; ABAQUS; Transmission; Regression; Empirical data